SOUTHEAST INSECURITY AND SUSTAINABLE NATIONAL ECONOMIC DEVELOPMENT IN NIGERIA - OKOREAFFIA; Okafo; Nwokorobia; Chinedum, (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Insecurity is a national challenge and a major implicative factor of varied worrisome issues in Nigeria. It has become daily reality of most parts of the nation, particularly the southeast region where incessant conflicts and social disorder create severe psychological, political and socio-economic dysfunctions. Southeast inhabitants face terrorization due to the chaos and violence associated with the activities of Indigenous People of Biafra (IPOB), the sit-at-home order and its related issues including kidnappings, farmers/herders clashes and other forms of criminality that cripple daily life and interactions in the area; culminating to a state of uncertainty, fear and low morale occasioned by the fierce gun battles and reprisal attacks between government forces, agitators and unknown clandestine groups. This precarious situation significantly paralyzes socio-economic endeavours in this domain of a people characteristic of renowned economic enterprise, and valued contributor, to Nigeria’s economic growth. The paper employs library research as methodology to explicate the state of insecurity in the southeast and how it undermines national economy of the country. It analyses the prevailing anarchic environment as strangulator of socio-economic life and activities with untold adverse effects on the productivity of the region and the nation, in an era of competitive global march towards sustainable development. The paper recommends effective reformation of the law enforcement agencies, good governance that addresses concerns of IPOB agitators and the zone; and other strategies for southeast stability and sustainable national economic advancement.